Equalização dinâmica de ganho para EDFAs empregados em redes ópticas reconfiguráveis - Nascimento, Vitor Vale do (2011)
Orientadores: Aldário Chrestani Bordonalli, Júlio César Rodrigues Fernandes de Oliveira